2022
DOI: 10.1111/cfs.12959
|View full text |Cite
|
Sign up to set email alerts
|

How are policies implemented in children's services? Developing an initial programme theory to evaluate the implementation of the new Child Sexual Exploitation guidance in Wales

Abstract: Although children's social care is an area rich in guidance, there is very little research looking at the implementation of new policies in the United Kingdom. In this article, we report on the first stage of a realist evaluation of the implementation of the new Safeguarding Children from Child Sexual Exploitation guidance in Wales. We discuss the development of an initial programme theory, for which we conducted semistructured interviews with practitioners and managers in three local authorities. We developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It is tentatively suggested it also demonstrates the extent to which organisational factors can hinder which co-produced outputs are embedded into practice. Usubillaga et al (2023) realist review found that implementation is complex and dependent on it being succinctly communicated to professionals and sufficiently different to local policies and current practice before it will be adopted. As the co-designed toolkit complements the local authority toolkit and existing policy it is possible that the co-designed solutions were not sufficiently innovative to encourage adoption.…”
Section: Discussionmentioning
confidence: 99%
“…It is tentatively suggested it also demonstrates the extent to which organisational factors can hinder which co-produced outputs are embedded into practice. Usubillaga et al (2023) realist review found that implementation is complex and dependent on it being succinctly communicated to professionals and sufficiently different to local policies and current practice before it will be adopted. As the co-designed toolkit complements the local authority toolkit and existing policy it is possible that the co-designed solutions were not sufficiently innovative to encourage adoption.…”
Section: Discussionmentioning
confidence: 99%